My hero academia 5: school briefs: Underground dungeon - Yoshi, Anri.; Cook, Caleb D.; Horikoshi, Kōhei, 1986- (San Francisco, CA : VIZ Media, LLC, 2021)
The students of class 1-A are getting ready for the end-of-the-year holidays but they get a big surprise when their big winter cleaning leads to a crazy discovery.
"Original story by Kohei Horikoshi."
"Shonen jump"--Back cover.
Incldes foldout page.
Translation of: Boku no hiro akademia.
Young Adult
English.
Keywords: Ability -- Juvenile fiction; Heroes -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Ability -- Fiction; Fantasy; Heroes -- Fiction; High schools -- Fiction; Schools -- Fiction; Ability -- Fiction; Heroes and heroines -- Fiction; High schools -- Fiction; School stories; Fantasy fiction; Light novels; School fiction